Effects of Defatted Rice Bran on Properties of Natural Rubber Latex Foam - มูลชัย, ดริญญา; เอี่ยมรัมย์, อรุณศรี (KKU Science Journal, 2013)
The effects of defatted rice bran (DRB) as a filler for natural rubber latex foam on its properties were investigated. The contents of DRB which pass through a 150-mesh screen used were 0, 10, 20, 30 and 40 phr. The maximum content of DRB that can be used as a filler for natural rubber latex foam was 30 phr. It was found that increasing amount of DRB showed a difficulty of making natural rubber latex foam. Gellation time, density, indentation force and compression set of DRB-filled natural rubber latex foam increased with increasing amount of DRB. However, the properties of natural rubber latex foam filled with 10 phr of defatted rice bran passed the standard specification of latex foam rubber according to TIS 173-2519. It can be graded equivalent to RU 20 with indentation force of 2.08 kPa and compression set of 9.20%. In addition, the cost of rubber compound having 10 phr of DRB which passed through a 150-mesh screen is lower than that of non-filled rubber compound about 14 baht / kilogram.